2010
DOI: 10.1363/3607210
|View full text |Cite
|
Sign up to set email alerts
|

STI Treatment-Seeking Behaviors Among Youth in Nigeria: Are There Gender Differences?

Abstract: The World Health Organization (WHO) estimates that more than three million new curable STI infections occur annually among people aged 15-49 worldwide-70% of those among 15-24-year-olds. 1,2 STIs can lead to major pregnancy complications, secondary infertility, and severe pain and discomfort. 3 In addition to being serious diseases in their own right, STIs can increase the risk of HIV acquisition and transmission by a factor of up to 10.In Nigeria, research on STIs among young people is limited, although there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 9 publications
10
14
1
Order By: Relevance
“…Suspected STD-infected subjects with higher education levels were also more likely to seek STD treatment in clinics, which corroborated previous studies [13, 14, 36, 37]. It indicates subjects with better education could be more knowledgeable about STDs and had more access to necessary STD education, resulting to their higher rates of clinic-based treatment seeking behaviour.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Suspected STD-infected subjects with higher education levels were also more likely to seek STD treatment in clinics, which corroborated previous studies [13, 14, 36, 37]. It indicates subjects with better education could be more knowledgeable about STDs and had more access to necessary STD education, resulting to their higher rates of clinic-based treatment seeking behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…Suspected STD-infected MSM with higher incomes were more likely to attend STD clinics, consistent with results from studies in Nigeria [36] and several Chinese cities [13, 14, 37]. Lower incomes was associated with poorer choices of treatment for STDs, for several reasons, including its correlation with lower educational level as well as unaffordable STD services and a general lack of appropriate healthcare resources in certain communities [24].…”
Section: Discussionsupporting
confidence: 79%
“…Due to the weak health infrastructure and lack of manpower, most countries in Africa have limited specialised clinics for prevention and treatment of STIs [16,17]. Some studies in Africa showed that people with STIs patronise pharmaceutical shops, patent medicine sellers, and traditional healers [18,19]. Additionally, adolescents and young people tend to engage in self-medication to avoid embarrassment and stigma at routine health clinics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there have been several studies that have examined adolescents’ STI treatment seeking behaviour. The majority of these studies show that adolescents opt first for self-treatment or in Sub-Saharan African countries, go to traditional healers 59 60. The most common reasons given for not seeking any treatment for STIs were ‘shame’, ‘did not feel it was necessary’, ‘financial problem’ and ‘heals automatically’ 59…”
Section: Introductionmentioning
confidence: 99%